Effect of moon phase during tides on variation of aquatic biodiversity in a tropical coastal lake of Anak Laut Lake, Aceh, Indonesia - AHMAD MUHTADI; RUSDI LEIDONALD; NUR ROHIM; MUH FIRDAUS (Society for Indonesian Biodiversity, 2025)
Abstract. Muhtadi A, Leidonald R, Rohim N, Firdaus M. 2025. Effect of moon phase during tides on variation of aquatic biodiversity in a tropical coastal lake of Anak Laut Lake, Aceh, Indonesia. Biodiversitas 26: 810-823. Anak Laut Lake, Aceh, Indonesia, is a coastal lake whose water dynamics are influenced by sea tides. It serves as a vital environment for marine life in Singkil and surrounding waters, functioning as a nursery and feeding grounds for prawns and fish larvae. This study was conducted from March to April 2023 at Anak Laut Lake in Gosong Telaga Barat Village, North Singkil District, Aceh Singkil District, Aceh Province, Indonesia. Sampling was conducted on four occasions during the tidal cycle: the new moon, first quarter, full moon, and last quarter. Aquatic biota samples were collected during both high and low tides. A Principal Component Analysis (PCA) multivariate analysis was performed using Microsoft Excel 2016 and Minitab. The nekton in Anak Laut Lake exhibited variations in space and time during high and low tides, with 29 families and 55 species identified. Benthic organisms included 26 species, classified into four distinct classes and 23 families. The abundance of phytoplankton was higher than that of zooplankton, reaching 90.96-95.30% of the plankton community. The larvae and juveniles discovered in Anak Laut Lake predominantly consisted of fish species from marine environments that reproduce in estuaries and seas and are transported into the lake by tidal currents. Fish population and diversity were higher during high tide due to the availability of habitats and the influx of marine fish. The tidal dynamics influenced the presence, abundance, and diversity of aquatic organisms in the lake. The new and full moon phases greatly affected the dynamics of the water quality and biodiversity of the lake due to the pronounced tidal ranges produced.